Implementation of missed call for making a password and controlling devices - Wahyu Wibowo, Ferry; ., . (International Journal of Engineering and Technology, 2018)
The cellular phones do not use telephone cables. The cellular phones send radio signals into the air to the nearest transmitter tower called the base station. The transmitter tower will emit the signal to the next station and so on until it reaches the phone that is called. When a new call arrives on the phone number, it will generate a tone until it is picked up, rejected, or the time has been ended to receive this tone (each telephone network provider has different policies related to the time used for this telephone connection so that this causes the number of rings raised to vary). This paper focuses on the missed call services which is one of the features found on the telephone. The tone that has been generated by this calling can emerge ring. This ring can be detected and manipulated to be something useful for controlling devices or making some password.Â Â